69 The ability of an artificial sweetener (Sucram®) to influence microbial community structure in the rumen papillae and content through the production of microbial-based neurochemicals. (5th December 2019) - Lyte, Mark; Koester, Lucas; Schmitz-Esser, Stephan
Abstract: The study of microorganisms to produce and utilize neurochemical signaling molecules that interact with the host is the emerging field known as microbial endocrinology. Production of these molecules can be regulated by several different environmental factors, including diet. The effect of artificial sweeteners on ruminant gastrointestinal tract microbiota and the ability of individual members to produce neurochemicals that may determine community composition and affect host physiology are unknown. To analyze whether an artificial sweetener (Sucram®, Pancosma, Switzerland) affects rumen content (RC) and rumen papillae (RP) microbiota, six fistulated, lactating Holstein cows were sampled before (baseline) and after exposure to Sucram®. 16S rRNA gene sequencing was conducted to identify Sucram®-induced microbial community changes. Additionally, ex vivo microbial cultures were used to identify neurochemical production in RP bacteria. Exposure to Sucram significantly increased the abundance of Operational Taxonomic Units (OTUs) belonging to Ruminobacter, Prevotella, Sharpea, Ruminococcus and Rikenella on the RP. These organisms have been reported to aid in digestion of feedstuffs and methane reduction, suggesting that Sucram® may induce beneficial shifts in rumen microbial communities. To gain preliminary insight into neurochemical production of RP microorganisms, we tested four different Lactobacillus isolates from RP for neurochemical production. We observed that the neurochemicals DOPAC (3, 4-Dihydroxyphenylacetic acid) and L-DOPA (L-3, 4-dihydroxyphenylalanine) were produced by three and four isolates, respectively. Ongoing experiments are evaluating the effects of Sucram® on neurochemical production in a larger number of rumen microbes. Overall, we observed significant differences in OTU abundance in response to the addition of Sucram®. Additionally, we confirmed that RP bacteria can produce neurochemicals. Both of these results are key to understanding how Sucram® modifies microbial communities within the rumen and possibly influences host physiology. Research into microbial endocrinology-based neurochemical signaling between rumen microbiota and their animal hosts may lead to advancement of livestock feed efficiency and welfare.